Transferring meaning in a context of multilingual lexicology and terminology - Martial AKPACA, Servais (Edelweiss Applied Science and Technology, 2024)
This paper aims to show that there is no perfect fit between the dictionary definition of a term and the various uses it is put to in different contexts, especially in a multilingual perspective. When a term is used repeatedly in various contexts, the concept it designates becomes wider and wider because its conceptual traits keep increasing. As a result, the definitions of the concepts that we find in dictionaries are not comprehensive. The concepts change with time whereas the terms that designate them do not change. Translating a term into a foreign language also widens up its lexical field because several denominations are sometimes used in the target language to account for a single SL term. The method used in this research is qualitative. It starts from the terms to get to the concepts and adopts a semasiological and cognitive approach. In specialised translation, the information on a particular term is contained in the texts in which it is used and these (texts) are the sole repositories of its meaning. One of the main findings of this research is that the interpretation of terms in various contexts leads to new definitions that are sometimes wider than the dictionary definitions. This research has also found that concepts are likely to change because the realities they refer to, change.